Unstable employment and health in middle age in the longitudinal 1970 British Birth Cohort Study. Issue 1 (27th March 2018) - Waynforth, David
Abstract : Evolutionary theory predicts increased fat storage and stress in response to unstable environments. Consistent with this, in a sample of middle-aged men and women in the UK, number of job losses experienced between ages 30 and 42 was associated with increased odds of diabetes diagnosis and high blood pressure. Evidence for an association between job losses and weight gain was less conclusive. Abstract: Background and objectives: Jobs for life have become increasingly rare in industrialized economies, and have been replaced by shorter-term employment contracts and freelancing. This labour market change is likely to be accompanied by physiological changes in individuals who have experienced little job stability. Evolved responses to increased environmental instability or stochasticity include increased fat deposition and fight-or-flight responses, such as glucose mobilization and increased blood pressure. These responses may have evolved by natural selection as beneficial to individuals in the short-term, but are damaging in the longer term. Methodology: This study tested whether job losses experienced between ages 30 and 42 are associated with increased body weight, hypertension and diabetes diagnosis in the 1970 British Birth Cohort, which consists of all registered births in a one-week period in April 1970. Results: Each job loss experienced increased the odds of developing diabetes by 1.39 times (CI 1.08–1.80), and of hypertension by 1.28 times (CI 1.07–1.53). Another economic variable, higher personal debt, was associated with all three of these health outcomes: every £100 000 of debt roughly doubled the odds of gaining at least 5 kg between ages 30 and 42. Conclusions and implications: These associations between job loss and health-risk factors suggest that our changing economy results in increases in the prevalence of risk factors for cardiovascular disease. At a broader level, they are consistent with evolutionary understandings of environmental stochasticity, and are a reminder that economic policy is also health policy.